Hematogone Hyperplasia Masquerading as Acute Lymphoblastic Leukemia With Concurrent Hypercupremia. Issue 7 (October 2020) - Naithani, Rahul; Jeyaraman, Preethi; Dayal, Nitin
Abstract : Alterations in copper homeostasis is an uncommon cause for hematologic alterations frequently presenting with dysplastic features in the bone marrow. Most of these alterations have been documented in adult patients with copper deficiency. Rare cases show hematogone hyperplasia in these patients. Effects of mild copper excess have not been documented in literature. We are describing a pediatric patient who presented with pancytopenia associated with hypercupraemia (excess of copper). Bone marrow examination showed hematogone hyperplasia. Interestingly, correction of serum copper levels with zinc therapy lead to complete improvement in pancytopenia. Hematogones had also reduced in subsequent marrow biopsy after therapy.